Natural and social consequences of military actions in the territory of Kharkiv region - Dmitriiev, Sviatoslav; Reshetchenko, Svitlana (Human Geography Journal, 2024)
This study is a continuation of long-term scientific work on studying the impact of climate change on the ecological state of water bodies with the involvement of a large array of statistical data for the period 1961-2020. But since in 2022 the studied territory became a theater of active war actions, it became necessary and scientific relevant to make a research about their impact on the state of water bodies. This is important in the context of changes in people’s living conditions, as water is a vital resource, especially in this region, where due to the specifics of water use and the speed of climate change, water resources have undergone a rather rapid degradation, and according to forecasts, Kharkiv region was to face problems of shortage of water resources already in the coming decades. Military operations have accelerated the deterioration of water bodies, and sources of drinking water are especially sensitive to such changes. Thus, in the city of Kharkiv, according to laboratory studies, out of 11 sources of drinking water, the water is suitable for consumption in only 1. To study changes in the state of water bodies, cartographic analysis was actively used, which makes it possible to assess the spatial distribution and differentiation of the speed of these changes, and to establish relationships between the factors affecting this, such as the location of the network of settlements and the concentration of the population, as well as the degree of proximity to the front line and intensity of shelling from all types of ballistic weapons. To determine the changes that took place after the beginning of the full-scale invasion due to the lack of statistical data from stationary monitoring points, data from satellite images were used. The scientific novelty of this research is the study of modern changes in the ecological state of water bodies and their comparison with previous changes due to the nature of climatic dynamics, since taking into account the proximity of the research object to the zone of active hostilities, scientific activity in this area is very complicated, and therefore Currently, studies on a similar topic are just beginning to appear, but they are fragmentary in nature, and therefore there is a scientific need to create a more comprehensive study.